2003
DOI: 10.1037/0893-164x.17.2.159
|View full text |Cite
|
Sign up to set email alerts
|

Spiritual beliefs, world assumptions, and HIV risk behavior among heroin and cocaine users.

Abstract: The relationship between spirituality and HIV risk behavior in a sample of 34 inner-city cocaine-using methadone-maintained patients was examined. Spirituality was operationally defined in terms of "life meaningfulness" and included the Santa Clara Strength of Religious Faith (T. G. Plante & M. T. Boccaccini, 1997b) and the World Assumptions Scale (R. Janoff-Bulman, 1989; assessing benevolence, meaningfulness, and worthiness of the self). Hierarchical multiple regression analyses of self-reported drug- and sex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(48 citation statements)
references
References 26 publications
(26 reference statements)
0
48
0
Order By: Relevance
“…The SCSRFQ has been found to predict sex related behavior among HIV cocaine-using patients [16] as well as better coping among alcohol dependent patients [17]. It has been used to predict forgiveness among marital couples [18] as well as among college students [9][10][11][12]21,23,24].…”
Section: Utilitymentioning
confidence: 99%
See 2 more Smart Citations
“…The SCSRFQ has been found to predict sex related behavior among HIV cocaine-using patients [16] as well as better coping among alcohol dependent patients [17]. It has been used to predict forgiveness among marital couples [18] as well as among college students [9][10][11][12]21,23,24].…”
Section: Utilitymentioning
confidence: 99%
“…Thus, it is unclear exactly how the scale might be used in various diagnostic and treatment facilities as well as in independent clinical practices. Since there is no cost in using the scale and since it was published originally in Pastoral Psychology but has been reprinted in several other outlets [1,16,18], it is impossible to know or to track who is using the scale and in what manner. There is, thus, no tracking mechanism employed to determine how the scale is being used since it is freely available to both professionals and the public for their use.…”
Section: Utilitymentioning
confidence: 99%
See 1 more Smart Citation
“…72 A perception that outcomes are just and can be controlled by personal behavior may support efforts to reduce HIV risk behaviors. 73 Faith or spiritual beliefs and practices, such as prayer, may be important for some individuals in their efforts to remain abstinent from substance use and to avoid risk behaviors for HIV infection. 72,74,75 One-third of our study participants indicated that they had changed their behavior because of their faith_s or church_s proscriptions.…”
Section: Religious or Spiritual Belief As A Coping Strategymentioning
confidence: 99%
“…While no known study has examined trauma and the world assumptions of convicted offenders, one published study examined the world assumptions on the risk behaviors of illegal drug users. Avants et al (2003) found that negative world assumptions significantly predicted sexual risk behaviors associated with HIV transmission; but not drug use risk behavior among a sample of 34 cocaine users (Avants et al 2003). However, this was a community sample, leaving the effect of negative world assumptions on the behavior of youthful offenders unknown.…”
Section: World Assumptionsmentioning
confidence: 97%